2013
DOI: 10.32607/20758251-2013-5-4-83-93
|View full text |Cite
|
Sign up to set email alerts
|

Alu- and 7SL RNA Analogues Suppress MCF-7 Cell Viability through Modulating the Transcription of Endoplasmic Reticulum Stress Response Genes

Abstract: 11% of the human genome is composed of Alu-retrotransposons, whose transcription by RNA polymerase III (Pol III) leads to the accumulation of several hundreds to thousands of Alu-RNA copies in the cytoplasm. Expression of Alu-RNA Pol III is significantly increased at various levels of stress, and the increase in the Alu-RNA level is accompanied by a suppression of proliferation, a decrease in viability, and induction of apoptotic processes in human cells. However, the question about the biological functions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
(58 reference statements)
3
11
0
Order By: Relevance
“…Nearly half of the human and other animal genomes are susceptible to transposition between different genomic loci (Finley, 2018). For example, Alu-retrotransposons comprise 11% of the human genome (Baryakin et al, 2013). Transcription of Alu-RNA and its evolutionary ancestor 7SL-RNA by RNA…”
Section: Dna Damage Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Nearly half of the human and other animal genomes are susceptible to transposition between different genomic loci (Finley, 2018). For example, Alu-retrotransposons comprise 11% of the human genome (Baryakin et al, 2013). Transcription of Alu-RNA and its evolutionary ancestor 7SL-RNA by RNA…”
Section: Dna Damage Responsementioning
confidence: 99%
“…Stress-induced transcription of these elements may be accompanied by an increase in the rate of their genomic transposition. It has been suggested that Alu/7SL transcripts contribute to the activation of key CSR functions such as cell cycle checkpoints and apoptosis (Baryakin et al, 2013).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Non-specific effects of Alu (i.e. effects that mirror those of 7SL RNA, from which Alu is believed to be derived) are observed (Baryakin et al, 2013;Herbert, 2019). Specifically, MCF-7 cells transfected with either Alu or 7SL RNA do not robustly induce interferon-inducible gene expression, but do show modulation of pro-apoptotic changes in expression of genes such as NUPR1, DDIT3 and FOXRED2 (Baryakin et al, 2013).…”
Section: Te Activity May Promote Mitochondrial Dysfunctionmentioning
confidence: 99%
“…An early study based on the transient transfection of HeLa cells with Alu -carrying plasmids showed an Alu -dependent inhibition of cell proliferation, yet this effect could not be demonstrated to be caused by Alu RNA [29]. More recently, Alu and 7SL RNA transfection into MCF7 breast adenocarcinoma cells was found to entail a decrease in viability and an induction of pro-apoptotic changes [30]. In another recent study, Alu RNA transfection into the SW480 colorectal cancer cell line was instead found to be without effect on cell viability and cell cycle distribution, yet to induce epithelial-to-mesenchymal transition [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Di Ruocco et al [27] found no perturbation of cell cycle distribution of colorectal cancer cells in response to the transient transfection of a synthetic Alu . On the other hand, Sakamoto et al [29] previously found that HeLa cell growth was inhibited after the transient transfection of endogenous and synthetic Alu sequences, and Baryakin et al [30] showed that the transient transfection of an Alu -RNA analogue suppresses cell proliferation and induces apoptosis of breast cancer cells. In line with this, Hu et al [31] reported an inhibition of stem cell proliferation after the microinjection of an AluSx overexpressing vector in Ntera2 cells; Morales-Hernandèz et al [32] showed that the transient transfection of the NANOG Alu sequence (localized upstream of the NANOG gene) repressed the expression of the pluripotency genes OCT4 and NANOG in Ntera cells; and Castelnuovo et al [33] reported a differentiation-promoting effect of an Alu -like RNA in neuroblastoma cells.…”
Section: Introductionmentioning
confidence: 99%